A Narrative Review of Medical Interpretation Services and their Effect on the Quality of Health Care. Issue 5 (May 2022) - Schlange, Stacie A.; Palmer-Wackerly, Angela L.; Chaidez, Virginia
Abstract : Extant literature has documented that language barriers have a negative effect on healthcare outcomes. This article provides an overview of research examining medical interpretation methods and their healthcare outcomes, interpreter use for low-English-proficient patients, and gaps in medical interpretation research and future directions. Abstract: Half of the foreign-born population in the United States speaks English "less than very well." The extant literature suggests that low-English-proficient (LEP) patients experience poorer healthcare outcomes than do language-concordant patients. It remains unclear which methods of interpreter services are best for communicating effectively and achieving positive health outcomes for LEP patients. This review examines interpretation methods to compare their effectiveness and frequency of use and identifies the remaining gaps in our knowledge. The evidence suggests that any type of professional language service is superior to untrained interpreting and vastly better than not using an interpreter at all. Even with this knowledge, use of interpreter services is unacceptably low and gaps remain. Further research is needed to isolate and examine different methods of interpretation and measure objective health outcomes. In addition, education is needed for interpreters and healthcare providers to ensure the most effective communicative strategies for LEP patients.